Association between METTL14 gene polymorphisms and risk of ovarian endometriosis - Zhou, Zijun; Jie, Youkun; Hu, Xianyue; Chen, Guange; Bao, Yanjing; OuYang, Zhenbo; Wu, Liangzhi; Gao, Tianyang; Zhang, Qiushi; Hua, Wenfeng (Frontiers in Genetics, 2025)
BackgroundEndometriosis, a prevalent chronic gynecological condition, is frequently associated with infertility and pelvic pain. Despite numerous studies indicating a correlation between epigenetic regulation and endometriosis, its precise genetic etiology remains elusive. Methyltransferase-like 14 (METTL14), a crucial component of the N6-methyladenosine (m6A) RNA methyltransferase complex and an RNA binding scaffold, is known to play a pivotal role in various human diseases. The possibility that single nucleotide polymorphisms (SNPs) in the METTL14 gene contribute to susceptibility of endometriosis has not been thoroughly investigated.MethodsWe assessed the genotype frequencies of five potential functional METTL14 SNPs (rs298982 G>A, rs62328061A>G, rs9884978G>A, rs4834698C>T, and rs1064034A>T) in a Chinese population consisting of 458 patients with ovarian endometriosis and 462 healthy controls. We employed unconditional logistic regression and stratified analyses to evaluate their genotypic associations with the risk of ovarian endometriosis.ResultsAmong the five SNPs examined, we found that the rs298982 A allele was significantly associated with increased risk, whereas the rs62328061 G allele was linked to a decreased risk of ovarian endometriosis. Individuals harboring two unfavorable genotypes demonstrated a significantly elevated risk of ovarian endometriosis (adjusted odds ratio (AOR) = 1.57, 95% confidence interval (CI) = 1.16–2.13, P = 0.004) compared with those with no risk genotypes. Stratified analysis revealed the risk effect of rs298982 GA/AA genotypes in the gravidity≤1, parity≤1, rASRM stage I, and rASRM stage II + III + IVsubgroups. Haplotype analysis showed that individuals with the GATAA haplotype were at higher risk of ovarian endometriosis (AOR = 5.54, 95% CI = 1.63–18.87, P = 0.006), whereas the AGTTG haplotype exhibited protective effects (AOR = 0.55, 95% CI = 0.31–0.97, P = 0.039) compared with wild-type GACAG haplotype carriers. Additionally, Bayesian false discovery probability and false positive report probability analysis confirmed the robustness of the significant findings. Expression quantitative trait loci analysis revealed a significant association between the rs9884978 GA/AA genotypes and elevated METTL14 mRNA levels in fibroblasts and adrenal gland. Conversely, the rs298982 GA/GG genotypes were significantly associated with reduced METTL14 mRNA levels in the nucleus accumbens and frontal cortex.ConclusionOur results demonstrate that METTL14 polymorphisms are associated with susceptibility to ovarian endometriosis among Chinese women.